PUTUSAN MAHKAMAH KONSTITUSI NOMOR 69/PUU-XIII/2015 DITINJAU DARI PEMENUHAN HAK-HAK ASASI MANUSI DAN ASAS-ASAS PEMBENTUKAN PERJANJIAN - Syaifullahi Maslul (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, Indonesia, 2016)
Marriage is spiritually bond between two people, both men and women to achieve a happy family. Marriage in Indonesia is a sacred thing. One implication is the mixing of property owned by both actors marriage. in setting the ground in Article 21, paragraph (1) and paragraph (3) and Article 36 paragraph (1) of Law No. 5 of 1960 about Agrarian, that land ownership is based on the principle of citizenship (nationality). The application of the articles a quo, participants referred to mixed marriages do not have land rights, as stipulated in Article 35 paragraph (1) of Law Number 1 of 1974 concerning marriage. despite having waived by the Directorate General of Law and Human Rights No. AM2-HA.01.02-10, in fact, Article 21 of Law No. 1 of 1974 concerning marriage be prohibitive. The Constitutional Court then issued a decision No. 69 / PUU-XIII / 2015 return guarantee protection of the rights of the perpetrator of mixed marriages.